Safety assessment of spray dried Strobilanthes crispus aqueous extract on liver, kidney and biochemical profiles in Sprague-Dawley rats - Nurul Amira Buslima; Sabariah Mohd Noor; Fauziah Othman; Asmah Rahmat (American-Eurasian Network for Scientific Information (AENSI), 2015)
Background: Nutraceutical products have been widely used nowadays to supplement for better health performance and scientiﬁc evidence on the safety level is important for consumption. Objective: Aim of this study was to evaluate the acute 14-days dose response toxicity of spray-dried Strobilanthes crispus aqueous extract supplementation on vital organ and important biochemical proﬁles. Materials and methods: Four different doses of spray-dried S. crispus (700, 2100, 3500 and 4900 mg /kg of body weight) were administered to 5 normal Sprague-Dawley rats to review and compare any possible changes in physical behaviour, biochemical parameters and organs morphology. Biochemical parameters tested include haematology, liver and kidney function tests. Result: Overall, there was no death and no signiﬁcant toxicity was observed with respect to biochemical parameters and organ morphology compared to normal control group. However, dosage group of 2100 - 4900 mg/kg of body weight showed signiﬁcant differences in sodium and chloride level as compared to control group. Abnormal morphological characteristics was found in liver tissues where the sinusoidal widening was found in dosage group of 3500 and 4900 mg/kg of body weight. Conclusion: in brief, ﬁndings on biochemical proﬁle of spray-dried S. crispus aqueous extract veriﬁed that it is safe to be consumed at the highest dose tested in this study (4900 mg/kg of body weight) and histological observations provide support to less or negligible destructive nature on liver and kidney tissues.